Migration and Media - Viola, Lorella; Musolff, Andreas (John Benjamins Publishing Company, 2019)
This four-part book explores the representational strategies used to frame current migration debates as crises of identity, collective and individual. It features fourteen case-studies of varying sets of data including print media texts, TV broadcasts, online forums, politicians' speeches, legal and administrative texts, and oral narratives.